Landscape and tourism in Mexcaltitán Island, Nayarit, Mexico - Zamudio Guerrero, María Guadalupe (2023)
The objective of this study was to analyze the most significant problems in relation to the landscape that were identified by the population of the island of  Mexcaltitán, Nayarit, Mexico, during the period 2019-2022. Data was gathered through semistructured interviews during the period of 2019-2022 and using the phenomenological thematic analysis method. The main findings suggest that the most representative problems are solid waste pollution, local impacts from the island’s infrastructure, and conflicts of interest with authorities related to tourism.